Scaffold-free 3D culture systems for stem cell-based tissue regeneration - Ke-Chun Liu; Yueh-Chen Chen; Chi-Fen Hsieh; Mu-Hui Wang; Meng-Xun Zhong; Nai-Chen Cheng (APL Bioengineering)
Recent advances in scaffold-free three-dimensional (3D) culture methods have significantly enhanced the potential of stem cell-based therapies in regenerative medicine. This cutting-edge technology circumvents the use of exogenous biomaterial and prevents its associated complications. The 3D culture system preserves crucial intercellular interactions and extracellular matrix support, closely mimicking natural biological niches. Therefore, stem cells cultured in 3D formats exhibit distinct characteristics, showcasing their capabilities in promoting angiogenesis and immunomodulation. This review aims to elucidate foundational technologies and recent breakthroughs in 3D scaffold-free stem cell engineering, offering comprehensive guidance for researchers to advance this technology across various clinical applications. We first introduce the various sources of stem cells and provide a comparative analysis of two-dimensional (2D) and 3D culture systems. Given the advantages of 3D culture systems, we delve into the specific fabrication and harvesting techniques for cell sheets and spheroids. Furthermore, we explore their applications in pre-clinical studies, particularly in large animal models and clinical trials. We also discuss multidisciplinary strategies to overcome existing limitations such as insufficient efficacy, hostile microenvironments, and the need for scalability and standardization of stem cell-based products.